Interactive Multimedia Development in Futsal Basic Techniques - Muhammad Iqbal; Moch Asmawi; James Tangkudung; Firmansyah Dlis; Surya Adi Saputra (Kazimierz Wielki University, 2019)
The purpose of this research is to develop some basic techniques and makeup products in the form of variations of exercises and training videos so that they can Easily be learned by the general public. In this study using the Research and Development Adopted method from borg and gall. The needs analysis was Carried out with 35 subjects as students who had passed the futsal course. Small group test with a sample of 12 people with good results then proceed to the large group stage with a sample of 40 people with good results and Proceeds to a PACT test with a total of 2 people and Obtained good results and can be used in actual practice. Based on the hypothesis testing and calculation criteria Obtained Sig. = 0036